Aberrant Expression of miR-1301 in Human Cancer - Zhong, Chenming; Dong, Yiyao; Zhang, Qiudan; Yuan, Chunhui; Duan, Shiwei (Frontiers in Oncology, 2022)
miR-1301 is a newly discovered miRNA, which is abnormally expressed in 14 types of tumors. miR-1301 inhibits 23 target genes, forms a ceRNA network with 2 circRNAs and 8 lncRNAs, and participates in 6 signaling pathways, thereby affecting tumor cell proliferation, invasion, metastasis, apoptosis, angiogenesis, etc. Abnormal expression of miR-1301 is often associated with poor prognosis of cancer patients. In addition, miR-1301 is related to the anti-tumor effect of epirubicin on osteosarcoma and imatinib on chronic myeloid leukemia(CML) and can enhance the cisplatin sensitivity of ovarian cancer. This work systematically summarizes the abnormal expression and prognostic value of miR-1301 in a variety of cancers, depicts the miR-1301-related signaling pathways and ceRNA network, and provides potential clues for future miR-1301 research.